Information System for Educational Resources Management - Sokoliuk, Vitalii; Hryhorovych, Viktor (My University, 2021)
Education is one of the best ways to form one’s personality so he is able to think and act independently. It has always been given a great importance. Education systems are constantly changing in order to adapt to new conditions and get the most out of them. Recently, self-education aimed at gaining knowledge related to cognitive interests or professional development has become increasingly popular. For this purpose, the relevant literature is studied, different lectures and research centers are attended, somebody`s own experiments and researches in the chosen field are conducted. Various methods on the Internet are rapidly developing. One of the most popular is learning on educational platforms.
Keywords: Education; studying; educational platform; self-education; online learning